Clinical importance of thrombocytopenia in patients with acute coronary syndromes: a systematic review and meta-analysis. (3rd October 2019) - Discepola, Vanessa; Schnitzer, Mireille E.; Jolicoeur, E. Marc; Rousseau, Guy; Lordkipanidzé, Marie
Abstract: Thrombocytopenia (TP) is common in hospitalized patients. In the context of acute coronary syndromes (ACS), TP has been linked to adverse clinical outcomes. We present a systematic review and meta-analysis of the evidence on the clinical importance of preexisting and in-hospital acquired TP in the context of ACS. Specifically, we address (a) the prevalence and associated factors with TP in the context of ACS; and (b) the association between TP and all-cause mortality, major adverse cardiovascular events (MACEs), and major bleeding. We conducted systematic literature searches in MEDLINE and Web of Science. For the meta-analysis, we fit linear mixed models with a random study-specific intercept for the aggregate outcomes. A total of 16 studies and 190 915 patients were included in this study. Of these patients, 8.8% ± 1.2% presented with preexisting TP while 5.8% ± 1.0% developed TP after hospital admission. Preexisting TP was not statistically significantly associated with adverse outcomes. Acquired TP was associated with greater risk of all-cause mortality (risk difference [RD]: 4.3%; 95% confidence interval [CI]: 2–6%; p  = 0.04), MACE (RD: 8.5%; 95% CI: 1–16.0%; p  = 0.037), and major bleeding (RD: 11.9%; 95% CI: 5–19%; p  = 0.005). In conclusion, TP is a prevalent condition in patients admitted for an ACS and identifies a high-risk patient population more likely to experience ischemic and bleeding complications, as well as higher mortality.